Flashcards on Reproductive Health Education for Elementary School Children: Development and Validation - Kusumaningrum, Tanjung Anitasari Indah; Kusumawati, Yuli; Inayati, Nurul Latifatul; Umaroh, Ayu Khoirotul; Hidayat, Muhamad Taufik; Livia, Wardhatul; Syifa, Asy; Trijaya; Nabilla, Nur Jihan Luthfia (Universitas Airlangga, 2025)
Reproductive health problems among children and adolescents are increasing. These problems can be prevented starting from a young age. Parents play a significant role in protecting children from sexual and reproductive health problems. Educational media are needed to improve parents' knowledge of reproductive health in elementary school age children so parents can provide this information to their children. Objective: To develop flashcards to support parents in educating children about reproductive health from an early age. Method: The study used a research and development method conducted from February-May 2024 in Kartasura, Sukoharjo. The ADDIE model was used as the stages in media development. One material expert and one media expert, ten parents in the small group evaluation, and 20 parents in the field evaluation tested the suitability of the media. This was followed by implementing media use with a one group pre- and post-test design involving 30 parents to assess the effectiveness of the media. The parents involved in this research were parents of elementary school children in grades 1-3. Data were collected using questionnaires. Data were analyzed using N-gain value. Results: Flashcard media was very suitable and effective (with the percentage of media feasibility in the experts’ assessment being 90%, small group evaluation 90.3% and 88.6% in the field evaluation). At the implementation stage, there was an increase in the average knowledge score before and after using flashcards with N-gain score was 0.43. Conclusion: Flashcards can be used for reproductive health education for parents of elementary school children.